“I speak English, but I’m still a Malay”: Language Attitudes and Identity amongst Bilingual Bruneians Living in London - Noorashid, Najib; McLellan, James (rEFLections, 2021)
This paper highlights the findings of a study into the language use, identity and attitudes of some Bruneian Malay government officers and students living in London. It is found that their allegiance towards the Malay language and Bruneian culture remains strong, despite their living in a largely Anglophone metropolis which requires them to communicate predominantly in English. As highly proficient bilingual speakers, the respondents are highly aware of the importance of maintaining their vernacular Brunei Malay as a marker of their identity. Through the use of observation and semi-structured interview methods, it emerges that predicted patterns of language shift towards the global language do not occur, and there is evidence of maintenance of strong Malay identity precisely because of their requirement to use more English in out-group communication contexts. The ‘zero-sum game’ notion, of more English equalling less Malay, is not applicable. This paper includes vignettes which show the participants negotiating between their languages in work and study contexts. It also demonstrates the need to consider how English interconnects with the other languages that are found in the repertoire of globally mobile South-East Asians.